(untitled) (Sains Humanika, 2005)
This paper focuses on the effort of developing rural society in line with a new philosophy of rural development or also known as the Second Transformation of Rural Development. Gerakan Desa Wawasan (GDW) or the Vision Village Movement concept was mooted to make a paradigm shift in attitude, practice, and inspiration among rural community in line with the objective of the Second Transformation of Rural Development and Vision 2020. The transformed rural society should be tough, self-reliant, innovative, knowledgeable, disciplined, confident, courageous, and able to use ICT. Realizing the importance of GDW in developing proactive and courageous Malaysians to face the challenging world today, the government decided to change the name of Gerakan Desa Wawasan to Gerakan Daya Wawasan to emphasize the move of a paradigm shift among rural community.